The Relationship Between Smartphone Addiction and Sleep Quality in Youth of GMIM “Eben Haezar” Kaaten Congregation - Greita Marya Selina Timpal (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Sleep is a vital process for human recovery, occurring predominantly during rest. High-quality sleep is essential for the recovery process, helping to alleviate excessive fatigue, while poor sleep quality can lead to reduced immunity. One significant issue affecting young people today is sleep quality, which is influenced by various factors, including smartphone use. This study aimed to investigate the relationship between smartphone addiction and sleep quality among the youth of the GMIM